2022
DOI: 10.1136/gutjnl-2022-328369
|View full text |Cite
|
Sign up to set email alerts
|

Production and possible reduction of greenhouse gases produced during GI endoscopy activity: a systematic review of available literature

Abstract: Background and aimsGreenhouse gases (GHGs) that trap heat in the atmosphere are composed of carbon dioxide (CO2), methane, nitrous oxide and fluorinated gases (synthetic hydrofluorocarbons, perfluorocarbons and nitrogen trifluoride). In the USA, the health sector accounts for 8.5% of total GHG emissions. The primary objective of this systematic review was to critically analyse the carbon emissions data from GI endoscopic activity.DesignThe GI endoscopy carbon cycle was evaluated at preprocedural, intraprocedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A 2022 systematic review summarized the available literature and found only 9 full fulllength articles. This indicates an urgent need for collecting systematic data on GI endoscopy emissions worldwide [15].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A 2022 systematic review summarized the available literature and found only 9 full fulllength articles. This indicates an urgent need for collecting systematic data on GI endoscopy emissions worldwide [15].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Expert consensus guidelines from various gastrointestinal societies have also been published, predominantly addressing issues related to endoscopy but also to the clinical practice of gastroenterology. [2][3][4] However, there are a number of unmet research needs in this field, and the evidence base for the recommendations in various guidelines, including the strategies for implementation of GHG reduction, is not very robust. There are very few randomised controlled trials evaluating the impact of one strategy over another.…”
Section: Introductionmentioning
confidence: 99%